2022
DOI: 10.1186/s12871-022-01626-4
|View full text |Cite
|
Sign up to set email alerts
|

ABO and RhD blood group are not associated with mortality and morbidity in critically ill patients; a multicentre observational study of 29 512 patients

Abstract: Background The ABO and RhD blood group represent antigens on the surface of erythrocytes. The ABO blood group antigens are also present on multiple other cells. Interestingly, previous studies have demonstrated associations between the blood group and many types of disease. The present study aimed to identifying associations between the ABO blood group, the RhD blood group, and morbidity and mortality in a mixed cohort and in six pre-defined subgroups of critically ill patients. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 32 publications
(30 reference statements)
0
9
1
Order By: Relevance
“…Blood type B was related to significantly higher risk of SARS-CoV-2 infection in some studies [ 59 , [68] , [69] , [70] , [71] , [72] , [73] ]; and a meta-analysis indicated that blood type B is associated with higher risk of SARS-CoV-2 infection in Asian, but not in European cohorts [ 74 ]. AB blood type, in turn, has been significantly related to either higher [ 47 , 62 , 68 , [70] , [71] , [72] , [73] , 75 ] or lower [ 59 , 61 ] risk of acquiring COVID-19.…”
Section: Associations Between Abo Blood Types and Covid-19mentioning
confidence: 99%
“…Blood type B was related to significantly higher risk of SARS-CoV-2 infection in some studies [ 59 , [68] , [69] , [70] , [71] , [72] , [73] ]; and a meta-analysis indicated that blood type B is associated with higher risk of SARS-CoV-2 infection in Asian, but not in European cohorts [ 74 ]. AB blood type, in turn, has been significantly related to either higher [ 47 , 62 , 68 , [70] , [71] , [72] , [73] , 75 ] or lower [ 59 , 61 ] risk of acquiring COVID-19.…”
Section: Associations Between Abo Blood Types and Covid-19mentioning
confidence: 99%
“…Latz et al also found that there was no relationship between the disease severity and blood groups, but the rate of COVID-19 positivity was higher in the B and AB blood groups 31 . In a recent multicenter observational study which involved 29,512 patients, AB blood group was the most frequently detected blood group in the COVID-19 cohort, and no correlation was found between blood types and disease morbidity and mortality 32 . In another newly published review, which comprises the highest number of cases so far, whereas there is little evidence of the relationship between blood types and COVID-19 disease severity; individuals with A blood group have a higher risk of developing the disease compared to O blood group 33 .…”
Section: Discussionmentioning
confidence: 92%
“…Groups B, AB, and RhD were not significantly associated with the outcome. Also, the study done by Kanderet al, 20 reported that ABO blood type and RhD status do not appear to influence mortality or morbidity in a general critically ill patient population. These findings should be interpreted with caution considering the high heterogeneity found between the studies when analyzing the risk of infection and the low or very low quality of the evidence.…”
Section: Discussionmentioning
confidence: 95%